The adult Drosophila malpighian tubules are maintained by multipotent stem cells. - Singh, S.R.; Liu, W.; Hou, S.X. (Cell Stem Cell, 2007)
All animals must excrete the waste products of metabolism. Excretion is performed by the kidney in vertebrates and by the Malpighian tubules in Drosophila. The mammalian kidney has an inherent ability for recovery and regeneration after ischemic injury. Stem cells and progenitor cells have been proposed to be responsible for repair and regeneration of injured renal tissue. In Drosophila, the Malpighian tubules are thought to be very stable and no stem cells have been identified. We have identified multipotent stem cells in the region of lower tubules and ureters of the Malpighian tubules. Using lineage tracing and molecular marker labeling, we demonstrated that several differentiated cells in the Malpighian tubules arise from the stem cells and an autocrine JAK-STAT signaling regulates the stem cells' self-renewal. Identifying adult kidney stem cells in Drosophila may provide important clues for understanding mammalian kidney repair and regeneration during injury.